Naturalist$1 (Bs guide to the birds of India: Bangladesh, Bhutan, Nepal, Pakistan and Sri Lankas - Grewal, Bikram; Bhatia, Garima (New Delhi Prakash Books, 2022)
This easy-to-use identification guide to the 280 bird species most commonly seen in India is perfect for resident and visitor alike. High quality photographs from one of India$1 (Bs top nature photographers are accompanied by detailed species descriptions which include nomenclature, size, distribution, habits and habitat.s
Keywords: Guide to Birds; Regional Birds